The Effectiveness Of Using Pbl-Based Cost Accounting Students' Textbook On The Cognitive Achievements Of Student Learning - Susilowibowo, Joni; Listiadi, Agung; Rochmawati, Rochmawati; Widayati, Irin (International Journal of Educational Research & Social Sciences, 2023)
Learning is an activity that is inseparable from human life. By learning, humans are able to develop the potential that they were born with so that they will be able to adapt to meet their needs. By learning, it is hoped that there will be changes in behavior in accordance with the expected goals. However, sometimes the expected changes in behavior do not occur and are not even in accordance with the expected goals, so learning difficulties are born. To help solve the problem of learning difficulties, among others, is to apply learning models that invite students to participate actively and are used to find out how to increase students' learning motivation in mastering certain competencies and the existence of teaching materials in the form of PBL-based textbooks. Along with the development of teaching materials in the form of PBLbased Cost accounting textbooks compiled in previous studies, it is necessary to test their effectiveness together with PBL learning models so that they can be a solution in overcoming lack of motivation and learning difficulties. This study resulted in a comparison of the PBL learning model using teaching materials in the form of a PBL-based Cost Accounting textbook with PBL using a reference book. The effectiveness of using PBL-based cost accounting textbooks needs to be tested to find out whether there is an improvement in the quality of learning. The sample in this study is Accounting Education students’ batch 2021. Comparison of the learning model with the use of PBL-based cost accounting textbooks is expected to be able to display the quality of interesting learning activities to observe. As for testing the comparison of this learning model using a True Experiment research design using an independent t test. Evaluation of learning media is an evaluation that has a special emphasis on user-oriented from the PBLbased Cost Accounting textbook. The results showed that there was a convincing difference in learning outcomes before and after using the PBL-based Cost accounting textbook.